ANALISIS KEPUASAN MAHASISWA PRODI S1 BIOLOGI FKIP UKI TERHADAP KINERJA DOSEN BIOLOGI DALAM MEMBERIKAN PELAYANAN PRAKTIKUM - Adisti Ratnapuri (Jurnal Pro-Life, 2017)
The quality management of biological laboratories can be detected through laboratory personnel evaluation that includes an evaluation of the quality of the laboratory, evaluation of student satisfaction as a practitioner, as well as the evaluation of the lecturer of biology, laboratory chief and head of the biology education courses as service providers practicum. This study aimed to analyze the satisfaction of practicum student of biology education S1 FKIP - UKI to quality of lecturer performance in providing service practicum. The usefullness of this research can be used as an evaluation of the quality of lecturer performance so that the results can be used for follow up as consideration in designing the management of the laboratory. Samples are students of Biology Education FKIP UKI third semester until seventh. The collection of data obtained by observation techniques, distribution of questionnaires and interviews. The data were collected and analyzed using descriptive methods percentage. The results of this study showed that the students of Biology Education FKIP UKI are satisfied with the services provided by a lecturer practicum.Keywords: student satisfaction, laboratories quality, management of biological laboratories quality, lecturer performance